Factors Influencing Unsafe Behavior in Somber Small Industry Centers (SIKS) Using Logistic Regression Analysis - Naibaho, Kevin Hotman Saulian; Chelsen, Chelsen; Jazil, Ridho Mufrih; Achmad, Rahadian; Anugerah , Muhammad Restu; Vindiari, Rendra Kristian; Damaiyanti, Siska; Malik, Anis Rohmana; Isabella, , Mayati (Riviera Publishing, 2024)
Tofu is a characteristic of Indonesian food, so it is not uncommon if this tofu food is found in Balikpapan City. Tofu is commonly produced in small and medium scale industries that are commonly found in the city of Balikpapan. The technology used in the tofu production process is still very simple, still uses human labor, and the process is less than optimal. The tofu production process begins with the washing, grinding, and pressing processes carried out by humans. This study aims to analyze the influence of the work environment and worker identity on Behavior Based Safety in the SIS tofu making industry. The population in this study is workers in SIKS somber totaling 32 workers from 14 home tofu production sites as for how to collect samples by direct observation and interviews with workers (response variables), namely unsafe behavior in the form of not wearing proper clothes while working (Y), and independent variables (predictors), namely a safe workplace environment (x1), Air Ventilation Conditions (X2) , Layout Conditions (X3), Working Duration (X4) Denoted 1 if > have worked for 3 months and 0 if < 3 months, worker status (X5), use of PPE in the form of boots (x6), educational status (x7) This study uses binary logistic regression analysis ?(x), where the workplace environment and workplace layout have the opportunity to have a significant influence on the unsafe behavior of workers (not wearing proper clothing) production workers know SIKS Somber.